[/IMG]i know how to derive when using the quotient rule but what about this one?
Follow Math Help Forum on Facebook and Google+
$\displaystyle \displaystyle y= \frac{3}{5r+11}\implies y' = \frac{(5r+11)\times (3)'-(5r+11)'(3)}{(5r+11)^2}$
thanks for the answer could you please explain the steps reasoning so i can get it.
Yep, I can, The quotient rule $\displaystyle \displaystyle y= \frac{u}{v}\implies y' = \frac{vu'-v'u}{v^2}$ Or you can say $\displaystyle \displaystyle y= \frac{3}{5r+11} = 3(5r+11)^{-1}$ then use the chain rule.
thank you very much i now see how you did it thanks a bunch
By the way, seeing as this is clearly a Calculus question, why have you posted it in Pre-Calculus?
I thought only university questions could go there? if that's wrong how do i move the thread?
To move the thread, report your own post using the Report Post tool at the lower left corner of the OP. Looks like a triangle with an exclamation mark inside it. A mod will move it for you.
View Tag Cloud